Production of subjectivities and school coexistence (Research, Society and Development, 2019)
This article aims to present the results of a study that sought to problematize the issue of school coexistence from the perspective of the construction of subjectivity. For that, a bibliographical research was carried out regarding the concept of subjectivity, looking for possibilities to broaden the reflection about the school coexistence. Thus, through a brief historical contextualization about the processes of construction of subjectivities and the school institution as we know it, it was possible to understand that this is configured as a space not only for transmitting objective knowledge from the disciplines, but also as a place of socialization in which all the subjects involved are subjectivated. It can be seen that the fragmentation of the school prevents the development of a global perception, leading to an increase in the degree of anguish, loneliness, isolation and consumerism, characteristic factors of subjectivity called capitalism. As a result of the fragility of the relationships, in school coexistence, there are frequent actions of exclusion, disrespect and resistance. Therefore, the need to think about democratic coexistence becomes fundamental for the construction of active subjects and increasingly able to take into account the values of the collectivity.